Oligosaccharide-Crowned hyperbranched poly(ethyleneimine) as an additive to thin-layer chromatography systems for the separation of vitamins, amino acids and β-blocker enantiomers - Dzema, Daria; Kartsova, Liudmilla; Kapizova, Diana; Tripp, Sandra; Polikarpov, Nikita; Appelhans, Dietmar; Voit, Brigitte (Jpc-Journal of Planar Chromatography-Modern Tlc, 2016)
Impregnation of a stationary phase by organic and inorganic agents in high-performance thin-layer chromatography (HPTLC) may result in higher separation selectivity and resolution. This work is devoted to the application of novel core-shell polymers consisting of hyperbranched (poly(ethyleneimine)) core surrounded by oligosaccharide shell (PEI-OS) as a component of silica stationary phase in HPTLC for the separation of water-soluble vitamins, amino acids, and chiral β-blocker enantiomers. The influence of polymer structure (degree of substitution of PEI terminal amino groups with oligosaccharides and molecular weight of dendritic core [5 or 25 kDa]) as well as the content of PEI-OS in the stationary phase and a method of modification of the stationary phase on the efficiency of vitamin and amino acid determination and on the enantioselectivity factors of β-blockers separation were investigated. It was established that such polymers can be used as modifying agents of HPTLC systems for on-line preconcentration of vitamins (B2) and amino acids (lysine, tryptophan, and glutamic acids). These polymers can also be recommended as chiral selectors for the effective TLC separation of β-blockers.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Amino acids; B-blockers; Chiral separation; High-performance thin-layer chromatography; Hyperbranched polymers; Vitamins